Methods for identifying and interpreting sex‐linked SNP markers and carrying out sex assignment: application to thornback ray (Raja clavata). (30th July 2020) - Trenkel, Verena M.; Boudry, Pierre; Verrez‐Bagnis, Véronique; Lorance, Pascal
Abstract: Sex‐determining modes remain unknown in numerous species, notably in fishes, in which a variety of modalities have been reported. Additionally, noninvasive individual sexing is problematic for species without external sex attributes or for early life stages, requiring cytogenetic or molecular analyses when sex chromosomes or sex‐linked markers have been characterized. Genomics now provide a means to achieve this. Here, we review common sex‐determination systems and corresponding statistical methods for identifying sex‐linked genetic markers and their use for sex assignment, focusing on single nucleotide polymorphism (SNP) markers derived from reduced representation sequencing methods. We demonstrate the dependence of expected sex assignment error on the number of sex‐linked SNPs and minor allele frequency. The application of three methods was made here: (a) identification of heterozygote excess in one sex, (b) F ST outlier analysis between the two sexes and (c) neuronal net modelling. These methods were applied to a large SNP data set (4604 SNPs) for 1680 thornback rays ( Raja clavata ). Using method (a), nineteen putative sex‐linked SNPs were identified. Comparison with the reference genome of a related species ( Amblyraja radiata ) indicated that all 19 SNPs are probably located on the same chromosome. These results suggest that thornback ray has a XX/XY sex‐determination system. Method (b) identified eight SNPs probably located on different chromosomes. Method (a) led to the lowest sex assignment error among the three methods (4.2% error for females and 3.7% for males).